ANALISA PENGARUH INFLUENCER DAN SOCIAL MEDIA MARKETING TERHADAP BRAND IMAGE SERTA DAMPAKNYA PADA PURCHASE INTENTION - I Gusti Putu Agung Widya Goca; Ni Putu Yuliana Ria Sawitri; Ni Putu Putri Ayu Wijayanthi (Bajang Institute, 2024)
Skincare has become a necessity for everyone, leading to intense competition in the industry. Understanding the factors that influence purchasing decisions is crucial. Social media influencers, social media marketing, and brand image are key elements affecting purchase intention. At Mutiara Permai Klungkung Shop, issues were found related to these factors. This study aims to analyze the influence of social media influencers and social media marketing on purchase intention, the impact of brand image on purchase intention, and the role of brand image as an intervening variable between social media influencers, social media marketing, and purchase intention. The research is quantitative, conducted at Toko Mutiara Permai Klungkung, with a sample of 180 customers who had never used Everwhite skincare. Data analysis includes outer model analysis, inner model analysis, and hypothesis testing using Smart PLS. Results show that social media marketing has a significant negative effect on brand image, while brand image indirectly mediates the influence of social media influencers and social media marketing on purchase intention